310-384 Washington Street, ca. 1920 - Unknown (Tufts Archival Research Center, 2005)
Elevated view of (left to right) 310-384 Washington Street. The facades of the buildings face west-northwest towards Washington Street. The steeple and southwest corner of the Old South Meeting House, located at 310 Washington Street at Milk Street, is visible along the center-right side of the photograph. Automobiles line Washington Street, and pedestrians fill the sidewalks. Flags adorn many of the buildings included in the photograph. The Custom House, located on State Street at India Street, is visible in the background of the photograph. 7 7/8 x 5 1/2 Photographs